Insight. Pre-Intermediate workbook - Sayer M. Mike (Oxford Exam Support)
The Workbook supports the lessons in the Student's Book with extra exercises for every lesson, a unit-by-unit wordlist with dictionary-style definitions, and a grammar reference and practice section which is linked to the grammar lessons in the Student's book. The Workbook also contains optional extra lessons and activities in the form of the Literature insight bank which will introduce your students to classic pieces of English Literature. The Exam insight sections offer preparation and practice for school leaving exams and the Workbook also contains a twenty page grammar and reference section that contains comprehensive grammar explanations and further practice.